(untitled) (The Pakistan Development Review, 2019)
Theoretically, fiscal deficit is inflationary but the sources of financing fiscal deficit may differ in terms of their impact on inflation. Question arises that what should be the least inflation cost source of financing? This study attempts to answer this question and explore the long run relationship among the sources to finance fiscal deficit and inflation. In so doing, the estimations have been done in four stages on the basis of categorisation of the deficit financing heads. In the first stage it has been tested that fiscal deficit along with money supply are inflationary. In the second stage fiscal deficit is bifurcated into two components, domestic borrowing and external borrowing for fiscal deficit. In the third stage, domestic borrowing is further divided into two heads, bank and non-bank borrowing. While in the fourth and last stage, bank borrowing is further categorised into two parts, borrowing from scheduled banks and central bank, and non-bank borrowing which comprises borrowing from National Saving Scheme for budgetary support. The Johansen Cointegration Technique is used for the first stage of estimation, while Auto Regressive Distributed Lag Model is employed for the rest of the three stages. The study finds that there is a long run relationship among sources of financing fiscal deficit and inflation. Inflation is positively affected by domestic borrowing, bank borrowing and borrowing from central bank, while central bank borrowing is more inflationary in nature. Consequently, fiscal deficit should be financed through external sources, non-bank and scheduled bank borrowings. JEL Classification: H62, H74, E31 Keywords: Deficit, State and Local Borrowing, Inflation